2005
DOI: 10.1111/j.1445-6664.2005.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior of itchgrass (Rottboellia cochinchinensis) in Peninsular Malaysia

Abstract: A glasshouse experiment was conducted at University Putra Malaysia, Serdang, to study the growth pattern of itchgrass collected from 13 locations. The itchgrass was either associated with crops or found along roadsides in six infested estates located in Johor, Kedah, Pahang, Perak, Perlis and Selangor. Significant differences between populations were observed in all variables except in time to seedling emergence. Cluster analysis of the data classified the populations into three major groups. The first group c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Itchgrass in Group A possessed some distinct morphological traits such as, the color (leaf sheath, stem and ligule), trichomes, size of seed (length and width), and 1,000 seed weight in comparison to the itchgrass samples in Group B. Plant height, number of leaves, number of seeds/plant, secondary culm diameter, and the weight of 100 intact or dehulled seeds were the most significant characteristics which provides strong evidence for the existence of three itchgrass groups in Peninsular Malaysia (Alloub et al, 2005). Even though the limitation of morphological traits for species classification is affected by both genetic and environment factors in identical conditions, the morphological traits do not differentiate from those of the itchgrass in the original region.…”
Section: Morphological Traitsmentioning
confidence: 76%
See 2 more Smart Citations
“…Itchgrass in Group A possessed some distinct morphological traits such as, the color (leaf sheath, stem and ligule), trichomes, size of seed (length and width), and 1,000 seed weight in comparison to the itchgrass samples in Group B. Plant height, number of leaves, number of seeds/plant, secondary culm diameter, and the weight of 100 intact or dehulled seeds were the most significant characteristics which provides strong evidence for the existence of three itchgrass groups in Peninsular Malaysia (Alloub et al, 2005). Even though the limitation of morphological traits for species classification is affected by both genetic and environment factors in identical conditions, the morphological traits do not differentiate from those of the itchgrass in the original region.…”
Section: Morphological Traitsmentioning
confidence: 76%
“…W.D. Clayton] is an annual upland weed, self-pollinated, and widely distributed in the tropical and subtropical regions (Alloub et al, 2005, Alves et al, 2003, Millhollon and Burner, 1993. It is a dominant species in some regions including Thailand where has a serious weed problem from itchgrass in several crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors reported waterhemp [Amaranthus tuberculatus (Moq.) Sauer], R. cochinchinensis, and Palmer amaranth (Amaranthus palmeri S. Watson) biotypes that exhibited diverse morphological traits, growth, sex ratio frequencies, and inflorescence emergence timings when grown in a common environment (Alloub et al 2005;Christopher et al 1989;Heneghan and Johnson 2017;Millhollon and Burner 1993;Pamplona and Mercado 1981;Spaunhorst et al 2018). Biotypes with fecundate reproduction and prolific growth may become more abundant and difficult to manage.…”
Section: Introductionmentioning
confidence: 99%
“…Rottboellia cochinchinensis, pertencente à família Poaceae (Gramineae), conhecida vulgarmente na língua inglesa por itchgrass e no Brasil por capim-camalote, é temida pelos agricultores de todo o mundo, sobretudo pelo seu poder de se dispersar, invadindo novas áreas, recebendo denominação de "caminhadora" em muitos países tropicais da América (Alloub et al, 2005). Quando presente, além de interferir diretamente, dificulta e encarece as práticas culturais e de manejo de diversas culturas (Bridgemohan et al, 1992).…”
Section: Introductionunclassified